## Conditional Probability – Problem (18/365)

A problem asks the following. The conditional variance of $\theta$ with respect to $\mathcal{D}$ is the random variable $\displaystyle V(\theta | \mathcal{D}) = E[(\theta - E(\theta | \mathcal{D}))^2 | \mathcal{D}]$

where $\mathcal{D}$ is a decomposition of the sample space. Show that $\displaystyle V\theta = EV(\theta | \mathcal{D}) + VE(\theta | \mathcal{D})$

We can read this as the follows. The variance of $\theta$ is the sum of the expectation of its conditional variances and the variance of the conditional expectations. For example, if $\mathcal{D} = \Omega$, then we ought to see a $0$ variance in the conditional expectations (since there is only one condition) $\displaystyle EV(\theta | \Omega) + VE(\theta | \Omega) \\ = EV\theta + VE\theta \\ = EV\theta + E(E\theta - EE\theta)^2 \\ = V\theta$

In general, the variance of conditional expectations expands to $\displaystyle VE(\theta | \mathcal{D}) \\ = E \left[ E(\theta | \mathcal{D}) - EE(\theta | \mathcal{D}) \right]^2 \\ = E \left[ E(\theta | \mathcal{D}) - E \theta \right]^2 \\ = E \left[ E(\theta | \mathcal{D}) \right]^2 - 2E \left[ E(\theta | \mathcal{D}) E \theta \right] + E(E\theta)^2 \\ = E \left[ E(\theta | \mathcal{D}) \right]^2 - (E\theta)^2$

and the expectation of conditional variances expands to $\displaystyle EV(\theta | \mathcal{D}) \\ = \sum_i E \left[ \left( \theta - E(\theta | D_i) \right)^2 | D_i \right] P(D_i) \\ = EE(\theta^2 | \mathcal{D}) - 2 E \left[ E(\theta | \mathcal{D}) E(\theta | \mathcal{D}) \right] + E \left[ E(\theta | \mathcal{D}) \right]^2 \\ = E\theta^2 - E \left[ E(\theta | \mathcal{D}) \right]^2$ $\displaystyle EV(\theta | \mathcal{D}) + VE(\theta | \mathcal{D}) \\ = E\theta^2 - E \left[ E(\theta | \mathcal{D}) \right]^2 + E \left[ E(\theta | \mathcal{D}) \right]^2 - (E\theta)^2 \\ = E\theta^2 - (E\theta)^2 \\ = V\theta$